Coffee conilon manuring with mineral fertilizer mixed granules, magnesium source, sulphur and micronutrients - Altoé, Arieli; Andrade, Felipe Vaz; Stauffer, Eduardo; Polidoro, José Carlos; Passos, Renato Ribeiro; Satiro, Lucas Santos (Coffee Science - ISSN 1984-3909, 2016)
This study aimed to evaluate the influence of the application of magnesium oxide associated with phosphogypsum and micronutrients (zinc and boron) in the form of granular fertilizer on the soil pH, calcium and magnesium in the soil, dry matter production and contents of calcium, magnesium, zinc and boron in plant, in an experiment carried out in a greenhouse. The experimental design was a randomized block with three replicates distributed in a split plot in time, the main plots consisting of six treatments (without fertilization control; N + P + K; phosphogypsum; magnesium oxide; phosphogypsum/MgO (70/30); phosphogypsum/MgO (70/30) + Zn + B); and the split composed of nine sampling periods. The results show higher levels of calcium (1.19 cmolc dm-3), magnesium (1.87 cmolc dm-3) and zinc (7.33 mg dm-3) in the soil for treatments with application of phosphogypsum, granulated phosphogypsum/MgO (70/30) and phosphogypsum/MgO (70/30) + Zn + B respectively. The application of phosphogypsum also shows higher calcium content (89.66 and 27.74 mg/plant leaves and stem, respectively) and higher dry matter production of leaves (11.22 g/plant), stem (5.67 g/plant) and roots (9.88 g/plant). Treatment with granulated phosphogypsum/MgO (70/30) show higher contents of magnesium (33.86 mg/plant), stem (13.36 mg/plant) and roots (62.97 mg/plant). The greatest contents in leaves B (2.83 mg/plant) and stem (0.24 mg/plant) are found in the treatment phosphogypsum/MgO (70/30) + Zn + B.